Innovation cycles and flexible automation in manufacturing industries - Sanchez, Angel Martinez (Technovation)
Flexible automation technologies have modified some of the assumptions of the Utterback and Abernathy model about the innovation life cycle. Using data from the Canadian manufacturing industries, this paper shows that high-technology industries are more intensively automated than other manufacturing industries, and also finds that the technological level and the growth of the industry are the best explanatory variables of automation intensity.